2018
DOI: 10.4317/jced.54610
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of variable bacterial colonization on coloured elastomeric ligatures during orthodontic treatment: An intermodular comparative study

Abstract: BackgroundBesides, other factors, the choice of materials used as orthodontic ligatures could be one of the many tools to counter the effects of microbial adhesion, that culminates into dental ailments. Therefore, we assessed bacterial adhesion on elastomeric ligatures with special reference to coloured elastomeric rings during orthodontic treatment.Material and MethodsA split mouth study, involving 240 samples of different elastomeric ligatures from forty orthodontic patients possessing good oral hygiene was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…The effects of fixed orthodontic appliances on dental plaque retention and microbial flora have been evaluated in previous studies . Many researchers have found the increased risk of white spot lesions due to increased microbial plaque accumulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of fixed orthodontic appliances on dental plaque retention and microbial flora have been evaluated in previous studies . Many researchers have found the increased risk of white spot lesions due to increased microbial plaque accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported increases in the amounts of cariogenic microorganisms including S mutans and Lactobacillus in the dental plaque and the saliva of patients after the bonding of orthodontic appliances. Similarly, we found a higher prevalence of S mutans than the other bacterial species in all archwires.…”
Section: Discussionmentioning
confidence: 99%
“…Different synthetic materials already were shown to provide a cozy microenvironment to harbour bacteria from anthropic, animal (e.g. Staphylococcus, Streptomyces, Nocardioldes , Hymenobacter ), or other natural sources ( Williamsia, Chryseobacterium, Rhodococcus ) (Mafu et al., 1990; Carniello et al., 2018; Sharma et al., 2018; Masoud, 2017). Therefore, a major factor driving beta-diversity variance in artificial surfaces may likely be due to contamination with human sweat or saliva as well as from the natural microflora in the surrounding area.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tried to highlight the associations based on the chemical characteristics of different elastic ligatures and the requirements of modifications for hampering the microbiological biofilm’s effects on oral health. Some studies have evaluated ligatures that release fluoride, but the results are varied and controversial: some highlight how, in particular, there is long-term ineffectiveness linked to the inability of the ligatures to guarantee a prolonged release over time; they also seem to be ineffective even against the decalcification [ 12 , 23 , 24 ].…”
Section: Orthodontic Elastomeric Ligaturesmentioning
confidence: 99%